Konsep Kebenaran dalam Perspektif Islam dan Barat (Studi Komparatif) - Dedy Irawan; Ridani Faulika Permana (Tasfiyah: Jurnal Pemikiran Islam, 2020)
This paper is written to discuss a problem of truth caused by westernization of knowledge in Islamic world. According to the western civilization, the truth is relative. Nothing is absolute. It is because they have made human as measurement of all things which have just been depending on fives senses and reason with philosophical speculation in secular life. The dichotomy of reality and truth could not be avoided. Therefore, this paper tries to explain the concept of truth in Islamic and Western view. Hopefully, this research could benefit all Moslem people to view the reality and the truth. It is absolutely urgent for a Moslem to know characteristic of Islamic concept of truth as the basis of the Islamic worldview such as concept of God, concept of man, and concept of nature.